2021
DOI: 10.1002/anie.202109705
|View full text |Cite
|
Sign up to set email alerts
|

Copper Pairing in the Mordenite Framework as a Function of the CuI/CuII Speciation

Abstract: Aseries of gas-phase reactants is used to treat aCuexchanged mordenite zeolite with the aim of studying the influence of the reaction environment on the formation of Cu pairs.The rearrangement of Cu ions to form multimeric sites as af unction of their oxidation state was probed by X-ray absorption spectroscopy( XAS) and also by applying advanced analysis through wavelet transform, am ethod able to specifically locate Cu-Cu interactions also in the presence of overlapping contributions from other scattering pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…10,12,16,18,30−34 In fact, the previous study has revealed using a special EXAFS analysis technique, e.g., EXAFS wavelet transform analysis, although it is difficult to evaluate Cu−Cu contributions from the usual EXAFS analysis. 25,29 The flow of wet He applied after this step caused almost no change in the first shell peak but a decrease in the second shell, suggesting that the interaction between Cu 2+ ions and the zeolite framework was partly disrupted because of ligand exchange with H 2 O under the wet gas flow conditions. After the reaction gas flow, the spectrum showed a slight decrease in the first shell peak at 1.5 Å, and the reduction gas flow caused a further decrease in the first shell peak.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…10,12,16,18,30−34 In fact, the previous study has revealed using a special EXAFS analysis technique, e.g., EXAFS wavelet transform analysis, although it is difficult to evaluate Cu−Cu contributions from the usual EXAFS analysis. 25,29 The flow of wet He applied after this step caused almost no change in the first shell peak but a decrease in the second shell, suggesting that the interaction between Cu 2+ ions and the zeolite framework was partly disrupted because of ligand exchange with H 2 O under the wet gas flow conditions. After the reaction gas flow, the spectrum showed a slight decrease in the first shell peak at 1.5 Å, and the reduction gas flow caused a further decrease in the first shell peak.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…However, note that this result does not deny the presence of Cu−Cu pairs in the Cu-CHA catalysts. 25,29 The Cu-CHA Cu single sites are not active species. 10,12,16,18,30−34 In fact, the previous study has revealed using a special EXAFS analysis technique, e.g., EXAFS wavelet transform analysis, although it is difficult to evaluate Cu−Cu contributions from the usual EXAFS analysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study by Deplano et al , the tendency of Cu ions to form ion pairs as a function of their oxidation state was discussed. 81 By performing a detailed wavelet transform analysis, a method enabling the discrimination of contributions overlapping in the R space if visualized by conventional FT-EXAFS, of the XAS data obtained on the same Cu-MOR sample, subjected to different redox pretreatments, the preference toward the formation of Cu neighbouring sites (Cu–Cu distance <3.5 Å) in the presence of Cu 2+ was proved. Cu + ions, instead, do not exhibit a clear mutual interaction fingerprint, testifying their tendency to segregate from each other within the zeolitic framework.…”
Section: Cu Mobility: Relation With Oxidation State and Ligands Coord...mentioning
confidence: 99%
“…Together with the conventional Fourier transform (FT)-EXAFS representation, we exploited a WT-based analysis 23 , 24 to unambiguously identify possible Cu–Cu scattering contributions possessing a characteristic lobe centered at ca. 7 Å –1 along the k direction 14 , 20 , 25 28 (SI, Section 3 for details).…”
mentioning
confidence: 99%